Map of day- and night-time heat stress-prone rice areas, 1992-2021 in the 3 deltas - Aunario, Jorrel; Paguirigan, Neale; Laborte, Alice G. (International Rice Research Institute, 2022)
Rice is highly susceptible to heat stress, particularly during the reproductive and ripening stages. Extremely high temperatures, even for a few hours, during flowering can cause complete sterility, while high temperatures during ripening can lead to reduced grain filling and poor milling quality. Using daily temperature data for the last 30 years (1992-2021) and maps of seasonal rice extent and cropping calendar, we mapped and characterized rice areas in the Mekong, Irrawady and Ganges Mega Deltas that are vulnerable to night-time and day-time heat stresses.